Temporalities embedded on the intensive body during the experience of the artistic project SoundSystem - Fasani, Priscilla Porto Nascimento (2019)
This article addresses the artistic project SoundSystem, developed by Franz Manata and Saulo Laudares since 1996. The process, in action up to the present day, consists of sharing experiences through sound installations, DJ’s performances and urban interventions. Universal signs such as heart beats and bird corners are used. The duo assumes an ethical concern to affect the participant. The main issues involved are the “good encounters”, the time-dilation and the intensity provoked by the dionysian impulses of music and dance. This text will discuss the possibility of experience the time of the event, resisting to chronopolitics.